(untitled) (Faridpur Medical College Journal, 2011)
Knowledge about the existing disease pattern and health seeking behavior is essential to provide need based health care delivery to any population and to make the health care system more pro-poor. A community based cross sectional study was conducted among 493 systematically selected households in the Modhukhali Upazilla of Faridpur District to determine the prevailing disease pattern and health seeking behavior in rural Bangladesh. Data were collected through face-to-face interview of the selected respondents. More than half of the respondents gave history of illness of her or her family members during the preceding 15 days. Fever (33.2%), gastrointestinal diseases (24.9%) and respiratory diseases (17.8%) were the most reported complaints. Overall, there were no discernible differences in the likelihood of seeking traditional or any kind of care considering socio-demographic variables and prevailing disease types. Occupation of household head as day labor or in agriculture and suffering from gastrointestinal diseases positively predicted use of para-professionals. Use of un-qualified allopths was negatively predicted by the male gender or literacy of the household head and presence of gastrointestinal, respiratory and other types of diseases and positively predicted by occupation of the household head in agricultural field or as day labor. Use of qualified allopaths was positively predicted by respiratory, skin/eye/ENT and other types of diseases and also by standard of living and relationship of the respondents with household head and negatively predicted by agricultural or day labor work of the household head. Existence of several distinct therapeutic systems in a single cultural setting was found to be an important feature of health care system in the study area. This study concluded that it is important to develop a need based health care delivery system and actions should be taken to improve the overall scenario of health system of rural Bangladesh. Key words: Disease pattern; health seeking behavior; rural area; Bangladesh DOI: 10.3329/fmcj.v6i1.7408 Faridpur Med. Coll. J. 2011;6(1): 32-37